Pengembangan Instrumen Identifikasi Diskalkulia Siswa Kelas VII di SMP Negeri 3 Bukittinggi - Alfia Mayfa Carissa; Tasnim Rahmat (Lembaga Yasin AlSys, 2026)
Dyscalculia is a specific learning disorder in mathematics that can affect students’ ability to understand number concepts, perform arithmetic operations, and solve mathematical problems; however, the development of dyscalculia identification test instruments based on indicators of linguistic skills, perceptual skills, and attentional skills among junior secondary school students remains limited. This study aims to develop a dyscalculia identification test instrument that meets the criteria of validity, reliability, practicality, and effectiveness as a diagnostic assessment tool for seventh-grade junior secondary school students. This study used a Research and Development approach with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved expert validators, mathematics teachers, and 32 seventh-grade students of SMP Negeri 3 Bukittinggi selected using purposive sampling. Data were collected through validation sheets, tests, practicality questionnaires, interviews, and documentation, and were then analyzed using quantitative descriptive analysis, item quality analysis, and qualitative data analysis. The results show that the developed instrument has a validity level of 77% in the valid category, a reliability coefficient of 0.916 in the very high category, a practicality level of 78% in the very practical category, and is able to identify students who show indications of dyscalculia based on aspects of linguistic skills, perceptual skills, and attentional skills. The conclusion of this study emphasizes that the developed dyscalculia identification test instrument is suitable for use as an initial screening tool to support the early detection of mathematics learning disorders, enabling teachers to design more appropriate learning interventions according to students’ needs. These findings contribute to the development of diagnostic assessment in mathematics education by providing an instrument with good psychometric quality and offer practical implications for teachers and schools in optimizing learning services and diagnostic assessment.